2019
DOI: 10.1002/hep4.1415
|View full text |Cite
|
Sign up to set email alerts
|

Liver X Receptor α–Induced Cannabinoid Receptor 2 Inhibits Ubiquitin‐Specific Peptidase 4 Through miR‐27b, Protecting Hepatocytes From TGF‐β

Abstract: Liver X receptor‐alpha (LXRα) acts as a double‐edged sword in different biological situations. Given the elusive role of LXRα in hepatocyte viability, this study investigated whether LXRα protects hepatocytes from injurious stimuli and the underlying basis. LXRα activation prevented hepatocyte apoptosis from CCl4 challenges in mice. Consistently, LXRα protected hepatocytes specifically from transforming growth factor‐beta (TGF‐β), whereas LXRα deficiency aggravated TGF‐β‐induced hepatocyte injury. In the Gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 34 publications
(42 reference statements)
0
6
0
Order By: Relevance
“…Cumulatively, CB2R stimulation decreased liver fibrosis by specifically decreasing IL-17 production by Th17 lymphocytes in a STAT5-dependent manner and decreasing the proinflammatory activity of IL-17 while conserving IL-22 production. Wu et al (2019) found that treating mice with JWH133 and CCL4 plus clodronate inhibited toxicant-mediated hepatic injury, as demonstrated by reduced levels of ALT, AST, apoptotic cells, caspase-3, and CREB. JWH133 also attenuated protein kinase A activity except in CB2-deficient mice, demonstrating that hepatocytic cells express functionally active CB2 downstream of the liver X receptors (LXRα).…”
Section: Alcoholic Liver Diseasementioning
confidence: 94%
See 1 more Smart Citation
“…Cumulatively, CB2R stimulation decreased liver fibrosis by specifically decreasing IL-17 production by Th17 lymphocytes in a STAT5-dependent manner and decreasing the proinflammatory activity of IL-17 while conserving IL-22 production. Wu et al (2019) found that treating mice with JWH133 and CCL4 plus clodronate inhibited toxicant-mediated hepatic injury, as demonstrated by reduced levels of ALT, AST, apoptotic cells, caspase-3, and CREB. JWH133 also attenuated protein kinase A activity except in CB2-deficient mice, demonstrating that hepatocytic cells express functionally active CB2 downstream of the liver X receptors (LXRα).…”
Section: Alcoholic Liver Diseasementioning
confidence: 94%
“…Comparing with another natural cannabinoid with high selectivity to CB2R, β-caryophyllene (BCP), which selectively and competitively interact with the CP55,940 binding site (i.e., THC binding site) of the CB2R, with 165-fold selectivity over CB1R, where it showed a weak partial agonism (Gertsch et al, 2008). JWH133 exhibits anticancer (Sánchez et al, 2001;Qamri et al, 2009), cardioprotective (Yu et al, 2019), hepatoprotective (Wu et al, 2019), gastroprotective (Tartakover Matalon et al, 2020), nephroprotective (Feizi et al, 2008), anti-inflammatory (Çakır et al, 2020), antihyperalgesic (Cabañero et al, 2020), and immunomodulatory activities (Zhu et al, 2019). It has also been demonstrated to exert neuroprotective effects in Parkinson's disease, ischemic stroke, depression, anxiety, Alzheimer's disease, epilepsy, and neuropathic pain (Kruk-Slomka et al, 2015;Sheng et al, 2019;Cao et al, 2020;Ivy et al, 2020;Jia et al, 2020;Jing et al, 2020;Zhao et al, 2020).…”
Section: Jwh133mentioning
confidence: 99%
“…Considering it in the liver, CB2R was identified mainly in Kupffer cells and stellate cells, and it is up regulated during pathology, especially occurring with inflammation such as NASH. However, the expression of this receptor in healthy hepatocytes is weak [30]. Although CBRs were believed to be functional only at plasma membranes, it is currently known that they are also expressed in intracellular organelle, e.g., mitochondria, where their role is not fully understood [31].…”
Section: Endocannabinoid System (Ecs)mentioning
confidence: 99%
“…Upon slicing the kidney samples, the tissue slices were fixed in 10% buffered-neutral formalin for 6 h. The samples were then stained with H&E, as previously described [ 43 ].…”
Section: Methodsmentioning
confidence: 99%